INTERPRETATION OF VLF MEASUREMENTS RELATED TO HYDROGEOLOGICAL SURVEYS - Vargemezis, G. (Bulletin of the Geological Society of Greece, 2007)
The aim of the application of VLF surveys in hydrogeology is the contribution to the decision making as concern the construction of a well. Geophysical survey by the application of VLF method must respond to the questions (a) if the construction of a well should be proposed or not, and if the answer is yes then (b) where exactly must be located. These answers are very crucial ones, since VLF methods is applied mainly in areas where bedrock is close to the surface and no chance has a well if it will not drill an aquiferous fault. Problems arise by the fact that the target to be detected is a conductive body which is interpreted as a fault filled with water. The major question that is posed to the surveyor is if the conductivity of the fault is caused by fresh water or by clay materials or saline water. Forward models of different resistivity contrast between host rock and conductive body have been computed and examined. Results show that interpretation of the imaginary part is very important to the evaluation of the data. Since the conductor -in the meaning of water presence onlymust be a medium one, a high value of the real part should be expected in parallel with a close to 0 value of the imaginary component which also must show one peak to the Fraser filtered data.